Soil magnetometry in the diagnosis of degradation processes - Kruglov, O.V. (AgroChemistry and Soil Science, 2020)
Soil degradation is the main challenge of our time. The task of agricultural science is to improve the methods of its research and monitoring. Magnetometric methods are notable among the numerous list of such methods due to the expressiveness and low cost. The purpose of the work is to show their informativeness in determining the processes that are factors in the degradation of arable soils. Methods of soil sampling according to DSTU 4287: 2004 and determination of humus content according to DSTU 4289: 2004 were used. For all samples, the specific MS was determined using a kappa-bridge KLY-2 according to the method of Evans (2003). The research was conducted in agricultural landscapes in Kharkiv and Poltava regions. Studies established highly informative results of determining the specific magnetic susceptibility of the soil when diagnosing erosion. The physical basis of such a diagnosis is the close correlation between magnetic susceptibility and humus content. This suggests the possibility of substituting the determination of the humus content for the determination of magnetic susceptibility (except for reference sections, based on which the interpolation and extrapolation of data). Hydromorphic and halomorphic processes also negatively affect the value of magnetic susceptibility. In this case, the correlation between it and the humus content is weak with the increase in the heterogeneity of the manifestations of degradation processes. Maps of magnetic characteristics make it possible to diagnose such manifestations, even in cases where it is not expressed in any way by the condition of the soil surface. Salt and hygromorphic processes significantly reduce the MS of both the upper soil horizon and soil-forming rocks, and the most significant reduction is associated with gleying processes. Thus, it is possible to differentiate not only agro-technological groups of soils but also soil-forming rocks.